The Relationship Between Academic Stress Levels and Insomnia among University Students - Fitrio Antony; Frisca Syarah Maharani; Elysa Apriliani; imel Ajeng Lestari (Health and Technology Journal (HTechJ), 2025)
Academic stress is a significant issue university students face, often arising from academic pressures such as deadlines, exams, and high expectations. These pressures disrupt mental and physical balance, leading to issues like insomnia, which can negatively impact students' health and academic performance. This study examines the relationship between academic stress levels and insomnia among university students, seeking to provide insights and practical recommendations for managing stress and improving sleep quality. A comprehensive review of 15 studies was conducted to analyze the connection between academic stress and insomnia. The research focused on various contributing factors, including academic workloads, social support, and environmental influences such as the COVID-19 pandemic. The findings indicate a significant relationship between academic stress and insomnia. Heavy academic workloads, tight exam schedules, and high faculty and parent expectations contributed significantly. Additionally, factors such as depression, anxiety, poor sleep hygiene, excessive digital device use, and unsupportive family dynamics were found to exacerbate sleep disturbances. The COVID-19 pandemic further intensified academic stress, leading to worsened sleep quality. While some studies found no direct correlation, they suggested that coping mechanisms, social support, and sleep habits might mitigate the impact of stress on sleep. Academic stress contributes significantly to insomnia among university students, affecting their quality of life and academic performance. Key triggers include heavy workloads, exams, and high expectations, worsened by poor sleep habits and technology dependence. The COVID-19 pandemic has further intensified these issues. Interventions in stress management, sleep habits, and mental health support are essential, with further research needed to explore the role of social support in reducing insomnia.